Virtual Pathology Elective Provides Uninterrupted Medical Education and Impactful Pathology Education During the COVID-19 Pandemic. (29th April 2021) - Fu, Lucy; Swete, Michael; Selgrade, Daniel; Chan, Clarence W.; Rodriguez, Raven; Wolniak, Kristy; Blanco, Luis Z.
As students do not qualify as essential health care workers, medical education faced severe disruptions during the COVID-19 pandemic including initial suspension of all in-person lectures and on-site rotations. Our Pathology Department was among the first at Northwestern to offer a completely virtual rotation with the goals of: (1) providing a comprehensive introduction to the practice of anatomic and clinical pathology, (2) emphasizing uninterrupted and continued excellence in education, and (3) minimizing exposure risk during the pandemic. The innovative 2-week curriculum incorporated diverse teaching modalities including live and recorded lectures; live and recorded video demonstrations; interactive small group discussions; interactive virtual sign-outs; and written and multimedia assignments, quizzes, and projects. The virtual elective ran from March to July 2020 with 52 total participating medical students. On post-rotation evaluations, students rated the pathology virtual elective 4.7/5.0 compared to other virtual rotations and 4.0/5.0 compared to all rotations (including in-person and virtual). Furthermore, continual improvements were made to the established framework based on rotation feedback such that curriculum content was more abundant and more favorably rated by the last cohort when compared to the first. Finally, although students identified interest in over 10 different medical specialties, all participants expressed increased interest in choosing pathology as a specialty and better understanding of pathology's role in patient care. We hope our detailed description of creating and evaluating a completely virtual elective rotation serves as a model for other departments to improve pathology education and visibility.